Meneladani Kehidupan Rasulullah Melalui Ayat-ayat Al-Qur'an - syahidah, syahidah (Maliki Interdisciplinary Journal, 2024)
This article examines how the verses of the Koran can be used as a guide to emulate the life of the Prophet Muhammad. The Prophet was known as a perfect role model with noble morals and wise actions. Through analysis of several verses of the Qur'an, this article explores important aspects of the Prophet's character and actions, such as patience, justice, compassion, courage, and wisdom in preaching. His patience was reflected in facing various trials, his justice and honesty were seen in every matter, his affection extended to all mankind, his courage in defending the truth, and his wisdom in conveying his da'wah. By emulating these values, Muslims can live better lives and become better individuals. This article emphasizes the importance of internalizing the teachings of the Koran and the morals of the Prophet in everyday life.